2021
DOI: 10.3390/biology10121264
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Unintentional Release of Feral Genetically Modified Rapeseed into the Environment

Abstract: Globally, the cultivation area of genetically modified (GM) crops is increasing dramatically. Despite their well-known benefits, they may also pose many risks to agriculture and the environment. Among the various GM crops, GM rapeseed (Brassica napus L.) is widely cultivated, mainly for oil production. At the same time, B. napus possesses a number of characteristics, including the ability to form feral populations and act as small-seeded weeds, and has a high potential for hybridization with other species. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 89 publications
0
13
0
Order By: Relevance
“…It is likely that the hybrids produced with feral S. bicolor in the roadside environments could in turn establish feral hybrid populations, with the ability of backcrossing with either of the parents occurring in these habitats, eventually leading to trait introgression (Ohadi et al, 2017 ). The establishment, persistence, and introgression of traits in feral oilseed rape in roadside environments have been widely reported (e.g., Bailleul et al, 2016 ; Crawley & Brown, 2004 ; Knispel et al, 2008 ; Sohn et al, 2021 ). In a study involving S. halepense × S. bicolor ( S. halepense as the female parent), Arriola and Ellstrand ( 1997 ) compared the F 1 hybrids with the S. halepense parent and observed that the hybrids did not differ from S. halepense in terms of tiller production, time of flowering, time to panicle production, pollen viability, fecundity, or biomass.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the hybrids produced with feral S. bicolor in the roadside environments could in turn establish feral hybrid populations, with the ability of backcrossing with either of the parents occurring in these habitats, eventually leading to trait introgression (Ohadi et al, 2017 ). The establishment, persistence, and introgression of traits in feral oilseed rape in roadside environments have been widely reported (e.g., Bailleul et al, 2016 ; Crawley & Brown, 2004 ; Knispel et al, 2008 ; Sohn et al, 2021 ). In a study involving S. halepense × S. bicolor ( S. halepense as the female parent), Arriola and Ellstrand ( 1997 ) compared the F 1 hybrids with the S. halepense parent and observed that the hybrids did not differ from S. halepense in terms of tiller production, time of flowering, time to panicle production, pollen viability, fecundity, or biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, the cropping area of genetically modified (GM) crops has constantly increased since 1996 [ 1 ]. GM crops cause huge nuisances to the environment, such as super weeds and introgressive hybridization.…”
Section: Introductionmentioning
confidence: 99%
“…It can spontaneously hybridize with B. rapa in both greenhouse and field experiments [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. One of the main issues in the cultivation of transgenic B. napus is that the transgene may have been transferred through hand pollination and/or spontaneously to their wild relatives/cultivars, with undesired ecological consequences that can increase the fitness and invasiveness of weedy populations [ 1 ]. Aside from that, GM crops and their transgenes spread via seed spillage during transportation and pollen-mediated gene transfers, resulting in feral populations [ 1 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The production has experienced over a 100-fold increase [1,2]. However, the main problem is potential transgene flow from GM crops that can affect non-transgenic counterparts, such as closely related or sexually compatible species [3]. Thus, the concerns about the gene flow from GM crops to their wild relatives have been intensified in the countries where their commercial cultivation is authorized.…”
Section: Introductionmentioning
confidence: 99%
“…have focused on crosses between transgenic B. napus (2n = 38; AACC) and wild relative B. rapa (2n = 20; AA) [5,23,24]. Spontaneous hybridization occurs in Europe and the United States, and their generations can easily backcross to B. rapa in wild environments [3,25,26]. However, limited information is known about the consequences of invasion between B. napus and B. rapa, and gene establishment is not well documented [27].…”
Section: Introductionmentioning
confidence: 99%